An evaluation of health workforce models addressing oral health in residential aged care facilities: A systematic review of the literature. (1st June 2020) - Chen, Rebecca; Irving, Michelle; Clive Wright, F.A.; Cunich, Michelle
Abstract: Background: In Australia and globally, there is an increasing problem of unmet oral health needs of older people above 65 residing in aged care facilities. Various workforce models have been trialled to implement oral health care programmes in aged care facilities, but the evidence behind these programmes and their underlying workforce models is not known. Objective: To systematically review the literature on the effectiveness, and economic feasibility of the current workforce models addressing oral care in aged care facilities. Methods: CINAHL, Cochrane CENTRAL, MEDLINE, EMBASE, EMB Reviews, NHS Economic Evaluation Database and grey literature were searched. Studies were included if they described an oral health workforce model with a clinical intervention and defined oral health outcome measures. Analysis was conducted using the NHMRC guidelines for scientific and economic evaluations. Results: Twenty‐eight studies were included. Four distinct workforce models of care were identified. 60% of the studies demonstrated short‐term effectiveness in clinical measures. Workforce models were similar in their effectiveness, with varying levels of quality within each model. Although three studies considered individual components of economic feasibility, only one provided a comprehensive economic analysis of both the costs and health outcomes. Conclusions Implications of findings: All workforce models of care had some positive impact on oral health for residents of aged care. Oral health should be included as a health focus in age care facilities. Future studies should include longer‐term health outcomes with rigorous economic analysis to ensure sustainably delivered workforce models of care for oral health management within aged care.